2005
DOI: 10.1063/1.1869416
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the shear horizontal mode in a monolayer by inelastic helium atom scattering

Abstract: Inelastic scattering of a low-energy atomic helium beam ͑HAS͒ by a physisorbed monolayer is treated in the one-phonon approximation using a time-dependent wave packet formulation. The calculations show that modes with shear horizontal polarization can be excited near high symmetry azimuths of the monolayer, in agreement with recent experiments. The parameters of the calculations are chosen to match the conditions of HAS experiments for triangular incommensurate monolayer solids of xenon, krypton, and argon ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…(11) of Ref. 4. This implies that the norm of the wave function 1 for having excited a single specific phonon mode is O(1/N) and very small.…”
Section: Approximating the Q-summentioning
confidence: 90%
See 2 more Smart Citations
“…(11) of Ref. 4. This implies that the norm of the wave function 1 for having excited a single specific phonon mode is O(1/N) and very small.…”
Section: Approximating the Q-summentioning
confidence: 90%
“…1,2 The theory is relatively complex because the processes that make a thermal energy He beam an exquisitely surface sensitive probe require treating the scattering as a strong coupling event. [3][4][5][6] For example, the simply commensurate monolayer solid p(1 × 1) H 2 /NaCl(001) is such a corrugated target that some experimental diffraction peaks are more intense than the specular peak 7 and the theory 6 shows this too. Further, that monolayer solid is so dilated that there is only a low potential energy barrier for the He to penetrate to the interlayer region that is between the plane of the monolayer molecule centers and the plane of the centers of surface ions of the substrate and there may be paths with no barrier for a more dilated conjectured commensurate monolayer solid p(1 × 1) H 2 /KCl(001) that has not yet been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The misalignment of the scattering plane relative to the ⌫M azimuth of the monolayer is ␣ = 2.6°, the Novaco-McTague orientational alignment angle at L nn = 4.33 Å determined in the Xe/ Pt͑111͒ experiments. 6 This value is not crucial because a misalignment ␣ = 0.5°also gives strong symmetry-breaking SH-mode excitation 9 Mostly, the phonon wave vectors are directed antiparallel to k iʈ because of the experimental experience 6 that this led to better resolved SH-mode excitation.…”
Section: F Interactions and Scattering Conditionsmentioning
confidence: 98%
“…An unanticipated result of the experiments was that all branches of the dispersion relations were accessed for wave vectors near high-symmetry azimuths in the first Brillouin zone. 6 In a previous paper, 9 denoted as Paper I, we demonstrated that the anomalous excitation of shear horizontal ͑SH͒ phonon modes by HAS from a physically adsorbed monolayer can be understood using a strong coupling inelastic scattering theory and known atomic interactions. The basic calculation was to generate the time-dependent solution for wave packet scattering, with the inelastic processes treated in the one-phonon creation approximation.…”
Section: Introductionmentioning
confidence: 99%